Corporate Social Responsibility : Private Self-Regulation is Not Enough - World Bank (Washington, DC, 2012)
Corporate social responsibility (CSR) has become an established part of the global landscape, with companies throughout the world abiding by the United Nations global compact and many governments starting CSR initiatives. Michel Doucin explains the history behind the phenomenon, identifying the pioneers, including those in emerging markets, and the different interpretations of CSR. He argues for the recently adopted genuine international rules to shape a universal CSR framework.